In vitro evaluation of antiurolithiatic activity of Euphorbia thymifolia L. plant extracts - Gupta, Asheesh Kumar; Dobriyal, Rishabh; Victorian, T. Dougnon (International Research in Medical and Health Sciences, 2018)
Objectives: The plant Euphorbia thymifolia Linn., Family: Euphorbiaceae, is used in traditional medical practices of India to treat various diseases. It was suspected and found to evaluate the effect of E. thymifolia plant extracts for in vitro antiurolithic activity on generated calcium oxalate crystals. Method: The aqueous, hydroalcoholic, and alcoholic (ethanolic) extracts of plant were tested for antiurolithiatic potential on generated calcium oxalate crystals by homogeneous precipitation method, and simultaneously, supporting two-step vice versa reactions were assessed (new method). The activity was assessed by studying the crystal dissolution by microscopy and quantitative alimental ions analysis for calcium and oxalates. Results: They exhibited significant activity when compared to standard drug cystone-polyherbal formulation. The aqueous and alcoholic extracts significantly decreased (P < 0.001) crystal size and increased calcium and oxalate concentration in reaction setup of all tested groups as compared to normal control. Simultaneously, a supporting two-step vice versa reaction was assessed which have shown a significant inhibition of crystal formation. Conclusion: All the interpretations of various result outcomes direct the use of this drug for urolithiasis prophylactic as well as curative treatments.